Optimisation & minimisation of corrosion rate of electroless Ni-Co-P coating. Issue 3 (2nd July 2020) - Sarkar, Subhasish; Baranwal, Rishav Kumar; Mukherjee, Arghya; Koley, Ishita; Biswas, Chanchal; Haider, Julfikar; Majumdar, Gautam
ABSTRACT: Electroless Ni-Co–P alloy coatings were deposited to decrease the corrosion rate of the copper substrate. Central Composite Design (CCD) was employed through Design Expert Software to establish optimised deposition parameters, which produces a coating having high corrosion resistance. CCD has also been employed to determine the effect of various process parameters namely concentration of cobalt sulphate (CoSO4 .7H2 O) solution (10–20 gm/cc), concentration of sodium hypophosphite (NaH2 PO2 .H2 O) solution (20–30 gm/cc) and bath temperature (80-90°C). The corrosion rate was determined by the Potential Dynamic test in 3.5% NaCl solution and the Tafel plot was used to determine the corrosion current density for each coated substrate. On the corrosion response of the coatings, the most significant interactions and important factors were identified using ANOVA analysis. The regression analysis showed a good fit of the experimental data through the second-order polynomial model with a coefficient of determination (R 2 ) value of 0.9531 and a model F-value of 22.57. 15 g/L of Cobalt Sulphate, 30 g/L of Sodium Hypophosphite and 80°C of bath temperature were found out to be the optimum conditions of bath deposition to obtain a corrosion rate of 0.535 µm/Y.